2022
DOI: 10.1136/gpsych-2022-100840
|View full text |Cite
|
Sign up to set email alerts
|

Echoes of the past: prevalence and correlates of PTSD among formerly abducted youths in northern Uganda: findings from the WAYS study

Abstract: BackgroundPost-traumatic stress disorder (PTSD) has considerable and persistent effects on survivors of war, particularly in postconflict areas. Yet, evidence on what keeps survivors on the path of PTSD remains scarce.AimsThe current study aimed to assess the prevalence and correlates of PTSD symptoms among the war-affected population in northern Uganda.MethodsData from 476 war-affected youths (aged 20–27 years) who had participated in a longitudinal cohort study were analysed to describe the enduring associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…PTSD is a long-lasting psychiatric disorder that occurs or is delayed after an individual experiences or witnesses an unusually catastrophic or threatening event[ 5 ]. Several studies[ 6 - 8 ] have shown that tumors have been identified as a source of traumatic stress, and the prevalence of cancer-related PTSD is estimated to range from 7.3% to 15.3%[ 9 ]. As young and middle-aged people play crucial roles in families and society, once diagnosed with cancer, they often have to face stress from a variety of aspects including illness, family, work place, and financial burden[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is a long-lasting psychiatric disorder that occurs or is delayed after an individual experiences or witnesses an unusually catastrophic or threatening event[ 5 ]. Several studies[ 6 - 8 ] have shown that tumors have been identified as a source of traumatic stress, and the prevalence of cancer-related PTSD is estimated to range from 7.3% to 15.3%[ 9 ]. As young and middle-aged people play crucial roles in families and society, once diagnosed with cancer, they often have to face stress from a variety of aspects including illness, family, work place, and financial burden[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Last, NIBS has exhibited significant clinical benefits in managing mental disorders like depression. 9 10 Military engagements frequently give rise to diverse physical and mental disabilities, such as post-traumatic stress disorder, 11 necessitating further exploration of the potential impact of NIBS in future investigations.…”
mentioning
confidence: 99%
“…They concluded that mental health issues could be reduced by adequate mental health laws and appropriate implementation. Amone-P'Olak et al 7 explored the prevalence and risks of post-traumatic stress disorder among war-affected youth in Uganda. They detected background and post-war environmental risk factors among them and highlighted the disastrous effects of war on young people's mental health.…”
mentioning
confidence: 99%